Tell Me a Story - Jonathan London (Richard C. Owen Publishers, 1998)
The author of "Froggy Gets Dressed" and other Froggy tales discusses his life, his daily activities, where he gets his ideas, and how he writes
Keywords: Circle Time Book - Biographies / Memoirs -- Circle Time Book - Biographies / Memoirs